Los efectos del señoreaje y el financiamiento por deuda pública sobre la inflación en Argentina, Venezuela y Colombia en el periodo 2000 - 2021 (2022)
This study aims to determine whether the different ways of financing the budget deficit have had any effect on inflation in Argentina, Colombia and Venezuela, in the period 2000 to 2021, since these economies have presented important fiscal deficits. For this purpose, a characterization of the mentioned variables is made and a VAR model is estimated for each country and their respective impulse-response functions. According to the results obtained, it can be inferred that seigniorage has significantly impacted inflation in Argentina and Venezuela, as well as public debt in both countries; while in Colombia none of the fiscal deficit financing mechanisms had any effect on inflation